Expression of Bioactive Chemerin by Keratinocytes Inhibits Late Stages of Tumor Development in a Chemical Model of Skin Carcinogenesis - Dubois-Vedrenne, Ingrid; De Henau, Olivier; Robert, Virginie; Langa, Francina; Javary, Joaquim; Al Delbany, Diana; Vosters, Olivier; Angelats-Canals, Edgar; Vernimmen, Maxime; Luangsay, Souphalone; Wittamer, Valérie; Parmentier, Marc (Frontiers in Oncology, 2019)
Chemerin is a multifunctional protein acting mainly through the G protein-coupled receptor ChemR23/CMKLR1/Chemerin1. Its expression is frequently downregulated in human tumors, including in melanoma and squamous cell carcinoma of the skin and anti-tumoral properties of chemerin were reported in mouse tumor graft models. In the present study, we report the development of spontaneous skin tumors in aged ChemR23-deficient mice. In order to test the potential therapeutic benefit of chemerin analogs, a transgenic model in which bioactive chemerin is over-expressed by basal keratinocytes was generated. These animals are characterized by increased levels of chemerin immunoreactivity and bioactivity in the skin and the circulation. In a chemical carcinogenesis model, papillomas developed later, were less numerous, and their progression to carcinomas was delayed. Temporal control of chemerin expression by doxycycline allowed to attribute its effects to late stages of carcinogenesis. The protective effects of chemerin were partly abrogated by ChemR23 invalidation. These results demonstrate that chemerin is able to delay very significantly tumor progression in a model that recapitulates closely the evolution of solid cancer types in human and suggest that the chemerin-ChemR23 system might constitute an interesting target for therapeutic intervention in the cancer field.